Evaluation of the association between lymph node ratio and long-term survival in patients after surgery for lymph node-positive bladder cancer: a SEER population-based study with external validation - Tao Chen; Xinchang Zou; Yihe Li; Lifen Peng; Zhen Song; Haichao Chao; Bin Fu; Tao Zeng (BMC Cancer)
Abstract Background The lymph node ratio (LNR) has been recognized as an emerging prognostic biomarker in various malignant tumors. Our study aimed to investigate the prognostic role of LNR in postoperative patients with lymph node-positive bladder cancer. Methods This study comprised a total of 3911 eligible patients diagnosed with lymph node-positive bladder cancer. This included 3767 patients from the Surveillance, Epidemiology, and End Results (SEER) database and 144 patients from two Chinese hospitals forming the external validation cohort. We used X-tile software to identify the optimal cut-off value for LNR. The Kaplan-Meier method and Cox regression model were utilized to evaluate the association between LNR and overall survival (OS) and cancer-specific survival (CSS). Based on the LNR index, two nomograms were constructed to estimate the prognosis of patients with lymph node-positive bladder cancer. The discriminant ability and accuracy of the nomogram were tested using the receiver operating characteristic (ROC) curve, calibration curves and decision curve analysis. Results The Kaplan-Meier survival curves, stratified by LNR, demonstrated significant differences in overall and cancer-specific survival rates (P < 0.05). After adjusting for clinical and tumor factors, including AJCC N staging, patients with an LNR greater than 0.3 exhibited significantly worse OS and CSS compared to those with an LNR less than 0.1 in both the SEER and external validation cohorts. Furthermore, the nomogram, which incorporated LNR, showed satisfactory discriminative ability, and the calibration curves confirmed favorable consistency. Conclusion LNR proves to be an independent prognostic factor for postoperative patients with lymph node-positive bladder cancer. These findings highlight LNR’s potential as a prognostic indicator, which could be beneficial in patient consultations and guiding treatment decisions.